Hospitalized children with SARS-CoV-2 infection and MIS-C in Jamaica: A dive into the first 15 months of the novel pandemic - Berry, Crista-Lee Shahine; Melbourne-Chambers, Roxanne Helene; Harrison, Abigail Natalie; Anzinger, Joshua James; Gordon-Johnson, Kelly-Ann Maxorinthia; Deyde, Varough Mohamed; Christie, Celia Dana Claire (Frontiers in Pediatrics, 2022)
COVID-19 in children was initially mild until the emergence of Multisystem Inflammatory Syndrome in Children (MIS-C). We describe pediatric COVID-19 in a developing country within the Caribbean. Jamaican children who were hospitalised with SARS-CoV-2 infection, in one Caribbean regional academic referral center during April 2020 through June 2021 were included. Prospective surveillance and pediatric infectious disease consultations were performed using the CDC’s MIS-C case definition. Data were extracted from patients’ hospital charts using WHO’s reporting form, entered into the RedCap database and SPSS 28 was used for analysis. MIS-C and non-MIS-C patients were compared using independent sample t-tests for continuous variables and Fisher’s Exact test for categorical variables, p values <0.05 were statistically significant. Seventy-nine children with COVID-19 with/without MIS-C presented to UHWI. Thirty-eight (48%) were mild ambulatory cases. Hospitalisations occurred in 41 (52%) children, of median age 10 ½ years. SARS-CoV-2 RT- PCR positivity was present in 26 (63%), IgM/IgG positivity in 8 (20%), with community exposures in 7 (17%). Eighteen (44%) MIS-C positive patients were significantly more likely than 23 MISC-negative patients (56%) to present with fever (94% vs. 30%; p<0.001), fatigue/lethargy (41% vs.4%; p=0.006), lymphadenopathy (33% vs.0%; p=0.003), elevated neutrophils (100% vs. 87%; p=0.024) and ESR (78% vs. 9%; p=0.002). Involvement of > two organ systems occurred more frequently in MISC-positive cases (100% vs. 34%; p<0.001), including gastrointestinal (72% vs.17%; p<0.001) with vomiting/nausea (39% vs. 9%; p<0.028); haematological/coagulopathic (67% vs. 4%; p<0.001); dermatologic involvement (56% vs. 0%;p<0.001) with mucositis (28% vs. 0%;p=0.001). MIS-C patients had Kawasaki Syndrome (44%), cardiac involvement (17%) and pleural effusions (17%). MIS-C patients had >4 abnormal inflammatory biomarkers including D-dimers, C-reactive protein, ESR, ferritin, troponins, lactate dehydrogenase, neutrophils, platelets, lymphocytes and albumen (72%). MIS-C patients were treated with intravenous immune gammaglobulin (78%), aspirin (68%), steroids (50%) and non-invasive ventilation (11%). None required inotropes/vasopressors. MIS-C negative patients received standard care. All recovered except one child who was receiving renal replacement therapy who developed myocardial complication. In this first report of COVID-19 from the Caribbean, children and adolescents with and without MIS-C were not very severe. Critical care interventions were minimal and outcomes were excellent.